Inter-religious Cooperation for HIV Prevention in Uganda: A Study among Muslim and Christian Youth in Wakiso District - Kagimu, Magid; Guwatudde, David; Rwabukwali, Charles; Kaye, Sarah; Walakira, Yusuf; Ainomugisha, Dick (religions, 2011)
Inter-religious cooperation has been recommended to address various issues for the common good. Muslims and Christians in Uganda are working together on HIV prevention in this spirit. A study was done to compare HIV prevalence and HIV-risk behaviors between Muslims and Christians. A total of 2,933 Christian and 1,224 Muslim youth between 15–24 years were interviewed and tested for HIV. The HIV prevalence was significantly lower among Muslims (2%) compared to Christians (4%). Muslims were more likely to be circumcised, avoid drinking alcohol and avoid having first sex before 18 years. These behaviors which may have led to lower HIV infections among Muslims are derived from Islamic teachings. Muslim religious leaders need to continue to emphasize these teachings. Christian religious leaders may need to consider strengthening similar teachings from their faith tradition to reduce new HIV infections among their communities. Muslims and Christians working together as good neighbors, in the spirit of inter-religious cooperation, can generate evidence-based data that may assist them to improve their HIV prevention interventions. By sharing these data each community is likely to benefit from their cooperation by strengthening within each religious tradition those behaviors and practices that appear helpful in reducing new HIV infections.
Keywords: Inter-religious cooperation; Muslims; Christians; Youth; HIV prevention; Uganda